Influence of NaNA3 and CuSO4 catalytic additives on coal oxidation process kinetic dependencies - Larionov Kirill B.; Mishakov Il’ya V.; Gromov Alexandr A.; Zenkov Andrey V. (MATEC Web of Conferences, 2017)
Experimental studies of bituminous coal and lignite oxidation were conducted with the addition of different nature catalytic additives: NaNO3 and CuSO4. The results showed that added mineral salts led to a noticeable decrease in the coals initial oxidation temperature and reaction acceleration at an early stage of the process.